The Polish People’s Republic in the context of elections to the European Parliament of the European Community (1979) - Barabasz, Adam (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2018)
The paper shows insight into the Polish response to the elections to the European Parliament held in 1979. It focuses on the opinions presented by journalists in the Polish press, and also highlights the response of the Ministry of the Interior of the Polish People’s Republic to the EEC’s political unification process announced after 1975. The paper also presents the response of the public in the EEC ‘nine’ to the important event that the elections to the European Parliament were.

W artykule przybliżono polskie reakcje na organizację wyborów do Parlamentu Europejskiego w 1979 roku. Skoncentrowano się na opiniach publicystów prasy polskiej, zwrócono także uwagę na reakcje Ministerstwa Spraw Wewnętrznych PRL na zapowiadany po 1975 roku proces unifikacji politycznej EWG. Przedstawiono również reakcje społeczeństw państw „dziewiątki” na niebagatelne wydarzenie, jakim były wybory do Parlamentu Europejskiego.
PRL wobec wyborów do Parlamentu Europejskiego Wspólnot Europejskich z 1979 roku
Keywords: European Parliament; elections; European Community; Polish People’s Republic; Parlament Europejski; wybory; Wspólnoty Europejskie; PRL